Characterization and enrichment of spermatogonial stem cells of common carp (Cyprinus carpio) - Vigoya, Angel A.A. [UNESP] (2024)
Spermatogenesis is a systematically organized process that ensures uninterrupted sperm production in which the spermatogonial stem cells (SSCs) play a crucial role. However, the existing absence of teleost-specific molecular markers for SSCs presents a notable challenge. Herein we characterized phenotypically the spermatogonial stem cells using specific molecular markers and transmission electron microscopy. Moreover, we also describe a simple method to suppress common carp spermatogenesis using the combination of Busulfan and thermo-chemical treatment, and finally, we isolate and enrich the undifferentiated spermatogonial fraction. Our results showed that C-kit, GFRα1, and POU2 proteins were expressed by germ cells, meanwhile, undifferentiated spermatogonial populations preferentially expressed GFRα1 and POU2. Moreover, the combination of high temperature (35 °C) and Busulfan (40 mg/kg/BW) effectively suppressed the spermatogenesis of common carp males. Additionally, the amh expression analysis showed differences between the control (26 °C) when compared to 35 °C with a single or two Busulfan doses, confirming that the testes were depleted by the association of Busulfan at high temperatures. In an attempt to isolate the undifferentiated spermatogonial fraction, we used the Percoll discontinuous density gradient. Thus, we successfully dissociated the carp whole testes in different cellular fractions; subsequently, we isolated and enriched the undifferentiated spermatogonial population. Therefore, our results suggest that probably both GFRα-1 and POU2 are highly conserved factors expressed in common carp germinative epithelium and that these molecules were well conserved along the evolutionary process. Furthermore, the enriched undifferentiated spermatogonial population developed here can be used in further germ cell transplantation experiments to preserve and propagate valued and endangered fish species.